Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1024/2008.03.03
|View full text |Cite
|
Sign up to set email alerts
|

Komorbidität bei Pathologischem Glücksspiel *

Abstract: Fragestellungen: Welche psychische Komorbidität liegt bei stationär behandelten pathologischen Glücksspielern vor, welches zeitliche Muster des Auftretens und welche Erkrankungswahrscheinlichkeit zeigt sich? Lassen sich Subtypen von Glücksspielern unterscheiden? </p><p> Methode: 101 Glücksspieler in stationärer Behandlung wurden mit dem DIA-X, der IPDE und der SCL-90-R untersucht. </p><p> Ergebnisse: Die höchsten Komorbiditätsraten (Zwölfmonatsprävalenz) zeigen sich für affektive Störun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 14 publications
1
13
0
2
Order By: Relevance
“…In conclusion, psychological distress seems to be positively associated with the intensity of treatment but not with treatment per se. These results correspond with findings from Premper and Schulz [8], who found anxiety disorder to be a predisposing factor for the development of a gambling disorder.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In conclusion, psychological distress seems to be positively associated with the intensity of treatment but not with treatment per se. These results correspond with findings from Premper and Schulz [8], who found anxiety disorder to be a predisposing factor for the development of a gambling disorder.…”
Section: Discussionsupporting
confidence: 81%
“…In Germany, comorbidity of psychiatric conditions has mainly been assessed in clinical settings. In a sample of 101 pathological gamblers receiving inpatient treatment, 91.1% had at least one Axis I disorder over their lifetime [8]. In a sample of 337 pathological gamblers receiving outpatient treatment, Braun et al [9] found that half of the study participants (47.4%) suffered from depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…). Additional data from N = 101 gamblers undergoing inpatient treatment were also incorporated into analyses (Premper & Schulz ). PG revealed high comorbidity rates with SADs, mood disorders, anxiety disorders and personality disorders, with SADs demonstrating the strongest comorbidity.…”
Section: Co‐occurring Disorders (Comorbidities)mentioning
confidence: 99%
“…It remains unclear whether decision‐making deficits in DG caused by SUD or DG itself considering that prevalence rates of SUD comorbidity in DG (Stewart and Kushner ) go as high as almost 60% (Black and Moyer ; Cunningham‐Williams et al. ; Premper and Schulz ; Lorains et al. ), with lifetime prevalence at 73% for alcoholism and 60% for smoking (Petry et al.…”
Section: Introductionmentioning
confidence: 99%